2023
DOI: 10.1097/j.jcrs.0000000000001033
|View full text |Cite
|
Sign up to set email alerts
|

Phase retardation and corneal sublayer thickness repeatability using ultrahigh-resolution polarization-sensitive OCT

Abstract: Design: Observational.Methods: In this study, all eyes were imaged using a custom-built ultrahigh-resolution PS-OCT and high-resolution hybrid OCT (MS-39). The repeatability of phase retardation en face maps and corneal sublayer thickness profiles was evaluated. The reflectivity and phase retardation were calculated from the 2 orthogonal polarization channels to generate en face maps of phase retardation and corneal sublayer thicknesses. 3 consecutive measurements of all participants were acquired for each eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Measuring not only the backscattering of light, but also the birefringence properties of the cornea, which are also dependent on its collagen structure, could provide new indices for disease characterization. A recent study demonstrated the excellent repeatability of phase retardation measurements with polarization-sensitive OCT, and better repeatability of epithelial thickness measurements than spectral domain OCT 33 . It is possible that combining different imaging modalities that measure different properties of the cornea could increase the accuracy in disease detection and the diagnosis of progression in keratoconus 30 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Measuring not only the backscattering of light, but also the birefringence properties of the cornea, which are also dependent on its collagen structure, could provide new indices for disease characterization. A recent study demonstrated the excellent repeatability of phase retardation measurements with polarization-sensitive OCT, and better repeatability of epithelial thickness measurements than spectral domain OCT 33 . It is possible that combining different imaging modalities that measure different properties of the cornea could increase the accuracy in disease detection and the diagnosis of progression in keratoconus 30 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Corneal layer thickness profiles across five different zones between 2–10 mm were also generated. Further details on generation of layer thickness mapping can be found in our previous work [ 12 ]. The PR and thickness en-face maps were smoothened by applying a floating average filter equivalent to 1 mm × 1 mm area of the cornea.…”
Section: Methodsmentioning
confidence: 99%
“…PS-OCT provides additional contrast by recording of tissue specific polarization changes [ 10 ]. Thereby, enabling measurement of phase retardation (PR) caused by form birefringence in aligned and reinforcing collagen fibrils [ 9 12 ]. We have evaluated asymmetric keratoconus in an earlier study and the findings were clearly able to differentiate between sub-clinical and clinical disease based on PR mapping [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, corneal phase retardation was reported to be sensitive to discriminate early KC [56]. Recent studies evaluated corneal phase retardation in healthy, thin, asymmetric KC, and clinical KC corneas, and showed higher phase retardation in clinical KC eyes [57,58].…”
Section: Anterior Segment Optical Coherence Tomographymentioning
confidence: 98%